Novel haptens synthesis and development of a monoclonal antibody-based enzyme-linked immunosorbent assay for leuco-malachite green in fish. Issue 6 (2nd November 2017) - Wang, Yu; Yang, Jinyi; Shen, Yudong; Sun, Yuanming; Xiao, Zhili; Lei, Hongtao; Wang, Hong; Xu, Zhenlin
ABSTRACT: To produce specific antibodies against leuco-malachite green (LMG), 15 haptens were synthesized and characterized, and conjugated to carrier protein for immunization. One antigen with excellent reactogenicity and immunogenicity was discovered. Specific monoclonal antibody with high sensitivity for LMG in competitive indirect enzyme-linked immunosorbent assay (ciELISA) was screened and selected. After the screening of a series of heterologous coating antigen and optimization of working conditions, the proposed ciELISA showed the 50% inhibition value (IC50 ) of 1.16 ng mL −1 and the limit of detection of 0.06 ng mL −1 for LMG. The average recoveries of LMG from spiked fish samples ranged from 78.0% to 101.0%, with coefficients of variation below 15%. Good correlation ( R 2  = 0.9977) was obtained between the results of ciELISA analysis and those of standard liquid chromatography–tandem mass spectrometry analysis. The proposed ciELISA is ideal for the rapid and sensitive detection of LMG with a low cost and high throughput.